Protective Effects of Celastrol on Diabetic Liver Injury via TLR4/MyD88/NF-κB Signaling Pathway in Type 2 Diabetic Rats - Li-ping Han; Chun-jun Li; Bei Sun; Yun Xie; Yue Guan; Ze-jun Ma; Li-ming Chen (Journal of Diabetes Research)
Immune and inflammatory pathways play a central role in the pathogenesis of diabetic liver injury. Celastrol is a potent immunosuppressive and anti-inflammatory agent. So far, there is no evidence regarding the mechanism of innate immune alterations of celastrol on diabetic liver injury in type 2 diabetic animal models. The present study was aimed at investigating protective effects of celastrol on the liver injury in diabetic rats and at elucidating the possible involved mechanisms. We analyzed the liver histopathological and biochemical changes and the expressions of TLR4 mediated signaling pathway. Compared to the normal control group, diabetic rats were found to have obvious steatohepatitis and proinflammatory cytokine activities were significantly upregulated. Celastrol-treated diabetic rats show reduced hepatic inflammation and macrophages infiltration. The expressions of TLR4, MyD88, NF-κB, and downstream inflammatory factors IL-1β and TNFα in the hepatic tissue of treated rats were downregulated in a dose-dependent manner. We firstly found that celastrol treatment could delay the progression of diabetic liver disease in type 2 diabetic rats via inhibition of TLR4/MyD88/NF-κB signaling cascade pathways and its downstream inflammatory effectors.